(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This research aims to identify the negative effects of illegal cockfighting at Barangay Gulod, Novaliches, Quezon City. Cockfights or “Sabong” is letting two roosters fight in an arena and betting on which wins. Regulation of live cockfighting in cockpit arenas is regulated by the Local Government Unit concerned. On the other hand, online sabong or e-sabong is regulated by the Philippine Amusement and Gaming Corporation (PAGCOR) and is currently allowed to legally operate e-sabong or online sabong at Lucky 8 Star Quest, owned by Atong Ang and Belvedere Corporation, owned by Bong Pineda. The researchers used the interview questions to gather and record information needed in the study. This study shows that illegal cockfighting addiction causes an uncontrollable urge to gamble more. Gambling addiction can be difficult to conceal, even if you gamble at home when no one is around. Your addiction may begin to show itself in other areas of your life.